KEPUTUSAN PEMBELIAN TERHADAP SEPEDA MOTOR HONDA BEAT: Studi Pada Konsumen Di Kecamatan Cinere, Depok - Dwi Noviani Putri, - (2019)
This study aims to analyze purchasing decisions on Honda Beat motorcycles in Depok. The population of this study were residents of Cinere Depok District and consumers of Honda Beat motorcycle users with a sample size taken as many as 75 respondents with the criteria of someone who had made a purchase of Honda Beat motorcycle. The sampling technique uses a purposive sampling method. The analysis technique used is PLS (Partial Least Square) with SmartPLS 3.0 software. The results of this study indicate that (1) Product quality has a significant effect on purchasing decisions of Honda Beat motorcycles in Depok with a t-test value of 30.559 > 1.994 and a significant value of 0.000 < 0.05, (2) Price has a significant effect on motorcycle purchase decisions honda beat in Depok with a t-test value of 2.713 > 1.994 and a significant value of 0.007 < 0.05 (3) Promotion has a significant effect on purchasing decisions of Honda Beat motorcycles in Depok with a t-test value of 3.828 > 1.994 and a significant value of 0.000 < 0.05. The results of the determinant coefficient (R2) are 99.6% that the value of R-Square (R2) > 0.75 constructs product quality, price and promotion.